Cells derived from iPSC can be immunogenic -- Yes or No - Cao, Jiani; Li, Xiaoyan; Lu, Xiao; Zhang, Chao; Yu, Honghao; Zhao, Tongbiao (Protein & cell, 2014)
The induced pluripotent stem cells （iPSCs）, derived by ectopic expression of reprogramming factors in somatic cells, can potentially provide unlimited autologous cells for regenerative medicine. In theory, the autologous cells derived from patient iPSCs should be immune tolerant by the host without any immune rejections. However, our recent studies have found that even syn- geneic iPSC-derived cells can be immunogenic in syn- geneic hosts by using a teratoma transplantation model （Nature 474：212-215, 2011）. Recently two research groups differentiated the iPSCs into different germ lay- ers or cells, transplanted those cells to the syngeneic hosts, and evaluated the immunogenicity of those cells. Both of the two studies support our conclusions that some certain but not all tissues derived from iPSCs can be immunogenic, although they claimed either ＂negli- gible＂ or ＂lack of＂ immunogenicity in iPSC derivatives （Nature 494：100-104, 2013; Cell Stem Cell 12：407-412, 2013）. To test the immunogenicity of clinically valuable cells differentiated from human iPSCs are emergenUy required for translation of iPSC technology to clinics.